Archaeological Landscape of the Lower Montane Region of Sri Lanka: Socio-Cultural Aspects of Archaeological Sites - Rambukwella, C. (Centre for Asian Studies, University of Kelaniya, 2015)
The objective of the research is to study the socio-cultural aspects of archaeological sites in the middle Mahaweli river basin which represents the lower montane region of the island. The area of study is significant in terms of its physiography. The present study area, the lower montane region of Sri Lanka, is demarcated for the purpose of the study as the area between 1000 – 3500 feet which is dominated by its own environmental factors. The Archaeological and historical evidence shows that the middle basin of the river Mahaweli has been thickly inhabited by humans since early Holocene. However, the knowledge about the development of human settlements of the region is scarce. This scarcity is crucially influential to understand the subsequent developments in the middle basin of the river Mahaweli towards its upper reaches. The middle part of the river basin has been neglected archaeologically during the last 100 years of research in the island due to some practical reasons. Hence, the previous studies on the ancient human settlements in Sri Lanka are confined to the coastal plains or the dry zone of the island. The textual information and cursory observations suggest that the middle Mahaweli basin has a great potential of cultural continuity from the pre- history up to the late historic periods. The filed data in this research will give support to understand the contribution of the early human settlements in the cultural development of the whole island throughout the history. In this context, almost all archaeological sites were directly connected to the socio-cultural aspects that were embraced by the settlements in the vicinity. Hence, those archeological sites will give an insight into the socio-cultural aspects of the heritage in the region.
Keywords: socio-cultural aspects; settlements; Sri Lanka; river basins